Specific detection of Staphylococcus aureus infection and marker for Alzheimer disease by surface enhanced Raman spectroscopy using silver and gold nanoparticle-coated magnetic polystyrene beads - Prucek, Robert; Panáček, Aleš; Gajdová, Žaneta; Večeřová, Renata; Kvítek, Libor; Gallo, Jiří; Kolář, Milan (Scientific reports, 2021)
Targeted and effective therapy of diseases demands utilization of rapid methods of identification of the given markers. Surface enhanced Raman spectroscopy (SERS) in conjunction with streptavidin-biotin complex is a promising alternative to culture or PCR based methods used for such purposes. Many biotinylated antibodies are available on the market and so this system offers a powerful tool for many analytical applications. Here, we present a very fast and easy-to-use procedure for preparation of streptavidin coated magnetic polystyrene-Au (or Ag) nanocomposite particles as efficient substrate for surface SERS purposes. As a precursor for the preparation of SERS active and magnetically separable composite, commercially available streptavidin coated polystyrene (PS) microparticles with a magnetic core were utilized. These composites of PS particles with silver or gold nanoparticles were prepared by reducing Au(III) or Ag(I) ions using ascorbic acid or dopamine. The choice of the reducing agent influences the morphology and the size of the prepared Ag or Au particles (15-100 nm). The prepare composites were also characterized by HR-TEM images, mapping of elements and also magnetization measurements. The content of Au and Ag was determined by AAS analysis. The synthesized composites have a significantly lower density against magnetic composites based on iron oxides, which considerably decreases the tendency to sedimentation. The polystyrene shell on a magnetic iron oxide core also pronouncedly reduces the inclination to particle aggregation. Moreover, the preparation and purification of this SERS substrate takes only a few minutes. The PS composite with thorny Au particles with the size of approximately 100 nm prepared was utilized for specific and selective detection of Staphylococcus aureus infection in joint knee fluid (PJI) and tau protein (marker for Alzheimer disease).
Keywords: dopamin; tau Proteins; proteiny tau; Magnetic Iron Oxide Nanoparticles; Spectrum Analysis, Raman; Polystyrenes; Streptavidin; Particle Size; Staphylococcal Infections; stříbro; Alzheimer Disease; Silver; magnetické nanočástice oxidů železa; stafylokokové infekce; polystyreny; Staphylococcus aureus; streptavidin; velikost částic; Humans; zlato; kyselina askorbová; biologické markery; Synovial Fluid; Dopamine; synoviální tekutina; Alzheimerova nemoc; Gold; Biomarkers; Ascorbic Acid; Ramanova spektroskopie; lidé